ALCOHOL PANIC, SOCIAL ENGINEERING, AND SOME REFLECTIONS ON THE MANAGEMENT OF WHITES IN EARLY APARTHEID SOCIETY, 1948–1960*. (29th October 2015) - Unknown
Abstract: The connection between ideologies of nation, alcohol abuse, and social engineering have not received systematic attention from historians. This article offers a case-study from the history of apartheid South Africa. Working around a fragment of apartheid history, a bureaucratic panic that excessive white drinking threatened the stability of the racial order, it explores geneaologies of state responses to white drinking in South Africa. It then concentrates on the role of Geoffrey Cronje, an intellectual / bureaucrat who not only drove the panic but then used it to implement new forms of social engineering in white South African society. Drawing on penal and welfarist traditions as well as medical models of treatment, he introduced a system for the discipline and correction of whites who drank heavily that drew on both state and private resources. I examine how the defiance of those incarcerated for drinking helped shaped subsequent, lighter-handed responses that managed the drinking of greater numbers of whites. This article may provide avenues for investigating alcohol abuse, state intervention, and social engineering in a range of mid-twentieth-century societies.